Proteinase‐activated receptor‐2 (PAR2) on blood pressure and electrolyte handling in the late pregnant rat. Issue 6 (12th May 2021) - West, David A.; Beck, Steven D.; de Souza, Aline M. A.; West, Crystal A.
Abstract : New Findings: What is the central question of this study? Pregnancy requires marked renal sodium and potassium retention and cumulative plasma volume expansion, in the setting of reduced blood pressure. Research in male rodents has shown that activation of PAR2 can produce peripheral vasodilatation, stimulate renal sodium chloride reabsorption and inhibit renal potassium secretion. Here, we investigate PAR2 activation in virgin and normal pregnant rats. What is the main finding and its importance? PAR2 expression and sensitivity to activation are increased in pregnancy. This implicates a possible role for PAR2 in supporting the renal/vascular adaptations of pregnancy required for normal maternal plasma volume expansion. Abstract: A healthy pregnancy involves renal and systemic haemodynamic adaptations, which allow renal sodium and potassium retention and cumulative plasma volume expansion, accompanied by a decline in blood pressure attributable to a reduction in the total peripheral vascular resistance. When these adaptations do not occur, pregnancy is compromised. The mechanisms permitting these opposing adaptations are largely unknown. Research in male rodents has shown that activation of PAR2 can produce peripheral vasodilatation, stimulate renal sodium chloride reabsorption and inhibit renal potassium secretion. Here, we investigate PAR2 activation in female virgin and normal late pregnant (LP) rats. We measured the mRNA expression of PAR2 in the renal cortex, outer medulla and inner medulla of virgin and LP rats using quantitative real‐time PCR. We also measured in vivo blood pressure, natriuretic and kaliuretic responses to PAR2‐activating peptide (SLIGRL‐NH2 ) in anaesthetized virgin and LP rats. We found that PAR2 mRNA was increased in the inner medulla of LP rats. We also found that LP rats had larger decreases in blood pressure and increases in net sodium retention compared with virgin rats. These findings suggest that pregnancy enhances sensitivity to the blood pressure‐lowering and sodium‐retaining effects of PAR2. Abstract :